TÜRK BASININDA ŞEYH SAİT İSYANI - DENİZ, MURAT (Fırat Üniveristesi, 2007)
Türkiye Cumhuriyeti Devletinin kurulmasından sonra siyasal ve sosyal alanda yapılanyeniliklerden bazı çevreler rahatsız olmaya başlamış, buna emperyalist devletlerin çıkarları daeklenince yurdumuzun bir köşesinde bu isyan patlak vermiştir.İsyana katılanlar başta İslam, şeriat ve halifelik adına hareket ederken isyanınhazırlanmasında etkili olanlar siyasi gayelerini de katarak olayı başka bir boyutakaydırmışlardır. Başlangıçta bu olayı basit bir ayaklanma şeklinde değerlendiren hükümet vebasın alınacak tedbirlerle kısa sürede bastırılacağı düşüncesindeydiler fakat gün geçtikçeolayın önemi anlaşılmış, hükümet daha sert tedbirler alırken basın da olaya daha geniş yervermeye ve halkı bilgilendirmeye çalışmıştır.Hükümetin kararlı tutumu, milletin ve basının desteği sayesinde isyan bastırılmış fakatkendinden sonra meydana gelecek isyanları ve günümüze kadar gelen bir kargaşayı mirasolarak da bırakmıştır.Anahtar Kelimeler: Cumhuriyet, hükümet, isyan, basın, haber

Certain circles became to get disturbed by the innovations which were released afterthe Republic of Turkey was found. This rebellion broke out in a certain region of our country,when the interests of the imperialist countries was on the carpet.The ones who participated the rebellion, started to act in the name of the Islam,Moslem religious law, and the caliphate in order to prepare a proper base for the rebellion.The ones who were influential in this context have added their political purposes, and havecaused the event to render in another dimension. The government and the press evaluated thisrebellion as trivial in the beginning, and they thought that this rebellion would be thwarted assoon as possible by taking the right steps at the beginning. However, the vehemence of theevent was felt harder day by day. The government took more decisive steps against therebellion and the press started to give more place to the rebellion, and tried to inform thepeople about it.The rebellion was depressed through the deliberate demeanor of the government, andthe support of the citizens and the press; however, it has bequeathed afterwards the rebellionsto be happen in the future and a contemporary chaos.Key words: Republic, Government, Rebellion, Press, News.
The rebellion of Şeyh Sait in the Turkish pres
Keywords: Tarih